Potential Of Zakat In Poverty Reduction In Indonesia: Literature Study - Asmaul Husna; Andri Soemitra (AGHNIYA : Jurnal Ekonomi Islam, 2022)
Zakat can be a useful tool for alleviating poverty in a location having a very large effect on the surrounding area. Poverty is one of the most pressing problems in Indonesia in terms of economic development. Since the majority of Indonesia's population is Muslim, one of the efforts to alleviate poverty is to utilize the potential of zakat. Apart from being the third pillar of Islam and a component of worship of mahdhah to Allah SWT, zakat is also a maliyah worship with various strategic social roles in improving the welfare of the people. This research is a qualitative descriptive study that uses a literature study approach to collect information from books, literature, theses, and library materials that are relevant to the research objectives. This literature review was conducted on 38 text publications between 2015 and 2021.